Heuristic method for multi-project finance-based scheduling - Elazouni, Ashraf (Construction Management and Economics, 2009)
A heuristic method is proposed for scheduling multiple projects subject to cash constraints. The heuristic determines cash availability during a given period, identifies all possible activities' schedules, determines the cash requirements for each schedule, ranks schedules based on the contribution to minimizing the increase in the project duration, schedules all activities of the selected schedule and determines the impact of the scheduled activities on the project cash flow. The effectiveness of the heuristic method was validated by comparing the results with the optimum results obtained by using the integer programming (IP) technique for 15 networks comprising up to 60 activities. The comparison indicated that the solutions obtained using the proposed heuristic are very comparable to the optimum solutions. An example of two concurrent projects was presented to demonstrate the proposed heuristic method. The proposed heuristic offers the ultimate flexibility to enter cash outflows and inflows at the actual occurrence time, the ability to rationalize the scheduling process, the flexibility to either devise or update schedules, and the ability to schedule practical-size multiple projects. Finally, this heuristic can be easily coded in software to help managers schedule projects under finance-constrained conditions.